2018
DOI: 10.1007/s10029-018-1816-y
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric inguinal hernias, are they all the same? A proposed pediatric hernia classification and tailored treatment

Abstract: Pediatric inguinal hernias are not the same and there is extreme variation in the presentation regarding the size of the defect. We proposed a nouvelle pediatric hernia classification modified from the original Nyhus classification for adult inguinal hernia with tailored surgical approach to each type (PHCTT). Applying this (PHCTT), it has the benefit of a significant reduction of recurrence rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 13 publications
0
5
0
1
Order By: Relevance
“…Also, in the recent study by Shehata et al [24] they reported that no recurrences had been detected in the follow-up. Also, Shehata et al [25] proposed classi cation for pediatric inguinal hernia according to size of internal ring. The average internal inguinal ring diameter was 7.7 mm ±1.5 SD (range of 5-10 mm), 16.7 mm±3.6 SD (ranging from 12 to 23 mm), and 22.6 mm ±4.6 SD (ranging between 16 and 33 mm) for Nyhus types PNI, PNII, and PNIII hernias, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, in the recent study by Shehata et al [24] they reported that no recurrences had been detected in the follow-up. Also, Shehata et al [25] proposed classi cation for pediatric inguinal hernia according to size of internal ring. The average internal inguinal ring diameter was 7.7 mm ±1.5 SD (range of 5-10 mm), 16.7 mm±3.6 SD (ranging from 12 to 23 mm), and 22.6 mm ±4.6 SD (ranging between 16 and 33 mm) for Nyhus types PNI, PNII, and PNIII hernias, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…[27] However, with better understanding, ner instruments, increased experience, and proper technique selection, the reported recurrence rates for laparoscopic hernia correction of (0.3% to 1.2%) were approached or became even lower than that of open repair. [25][26][27] There are many factors linked to hernia recurrence in laparoscopy. For example, incomplete separation or leaving an intact peritoneal gap above the vas and vessels in boys to avoid their injury, loose knot, use of absorbable suture in purse-string suturing without separation techniques, and large defects without narrowing the IIR, are very important causes for recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…There is no consensus definition of a wide ring, and our definition is based on experience. A recent article by Shehata et al 14 proposed pediatric Nyhus (PN) classification system for a tailored treatment of pediatric inguinal hernias. Along with herniotomy, the authors recommended narrowing of deep ring for PN type II and IPT repair for PN type III hernias.…”
Section: Discussionmentioning
confidence: 99%
“…(4) En ocasiones, sobre todo cuando se trata de hernias pequeñas, no se hace evidente al examen físico la hernia que refieren los familiares; en tal caso, se le indica al paciente que tosa, puje, se ponga en cuclillas o salte, esto hará que aumente la presión intraabdominal y que salga el contenido herniado. (5,6) AFECCIONES…”
Section: Manifestaciones Clínicasunclassified